2019
DOI: 10.3389/fcvm.2019.00080
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Thrombocytopenia: Update on Genes and Genetic Variants Which may be Associated With Bleeding

Abstract: Inherited thrombocytopenia (IT) is comprised of a group of hereditary disorders characterized by a reduced platelet count as the main feature, and often with abnormal platelet function, which can subsequently lead to impaired haemostasis. Inherited thrombocytopenia results from genetic mutations in genes implicated in megakaryocyte differentiation and/or platelet formation and clearance. The identification of the underlying causative gene of IT is challenging given the high degree of heterogeneity, but importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 81 publications
(70 reference statements)
1
41
0
6
Order By: Relevance
“…Nevertheless, as a guideline for genetic studies in a single patient, it has been proposed to ascribe a novel genetic mutation as the cause of the observed phenotype (Casanova et al , ). Our study has fulfilled this guideline with analyses to exclude reported genetic causes of IT in our patient (Almazni et al , ; Lentaigne et al , ) and identification of a homozygous frameshift mutation of NF‐E2 which would impair the function of the protein, as well as previous reports of relevant animal phenotypes of severe thrombocytopenia due to loss of p45/NF‐E2 function (Shivdasani et al , ; Levin et al , ; Shyu et al , ).…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Nevertheless, as a guideline for genetic studies in a single patient, it has been proposed to ascribe a novel genetic mutation as the cause of the observed phenotype (Casanova et al , ). Our study has fulfilled this guideline with analyses to exclude reported genetic causes of IT in our patient (Almazni et al , ; Lentaigne et al , ) and identification of a homozygous frameshift mutation of NF‐E2 which would impair the function of the protein, as well as previous reports of relevant animal phenotypes of severe thrombocytopenia due to loss of p45/NF‐E2 function (Shivdasani et al , ; Levin et al , ; Shyu et al , ).…”
supporting
confidence: 58%
“…Inherited thrombocytopenias (IT) are genetic diseases that affect platelet production and function, resulting in thrombocytopenia and a tendency for bleeding. Novel genetic mutations responsible for IT are being reported continuously (Almazni et al , ; Lentaigne et al , ). We present a case of thrombocytopenia with a homozygous frameshift mutation of nuclear factor, erythroid 2 ( NF‐E2 ), which has not been reported before.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After the evaluation using the three software packages ( sift , polyphen and mutationtaster ), only one SNV remained to be consistently predicted as a damaging variant (Table ). Moreover, with the assistance of the ThromboGenomics project, we did not find any pathogenic variants within this family located in the 96 genes and the previously reported SBF2 gene associated with inherited bleeding, thrombotic, coagulation and platelet disorders. This identified damaging SNV is a missense change named as chr19: g.15170364G>A based on the GRCh38 version in the NOTCH3 gene according to the Human Genome Variation Society (HGVS) guidelines (http://www.hgvs.org/mutnomen/), which results in the change at postion 1694 of Arg into Gln within a region linking the NODP domain and the ANK domain of the protein.…”
Section: Resultsmentioning
confidence: 45%
“…The inherited platelet disorders that are diagnosed in adults are usually non-syndromic at birth and do not or induce only mild spontaneous bleeding complications, in contrast to those diagnosed in childhood [24]. To date, more than 30 inherited disorders, derived from 50 gene defects have been identified and have been reviewed in detail elsewhere [16,17,24,26]. Tables 2 and 3, respectively.…”
Section: Anomalies Of Platelet Morphology In Inherited Platelet Disormentioning
confidence: 99%